ANALISIS PERLINDUNGAN HAK MORAL DAN HAK EKONOMI PEMEGANG HAK SENI INSTALASI (STUDI PUTUSAN NOMOR 19 PK/PDT.SUS-HKI/2023): Analysis of Moral and Economic Rights Protection for Installation Art Copyright Holders in Decision No. 19 PK/PDT.SUS-HKI/2023 - Kevindra Akiko Meliala; Simona Bustani (Faculty of Law, Universitas Trisakti, 2025)
Legal events involving copyright infringement often cause losses to the creator and additional parties involved. Based on Decision Number 19 PK/Pdt.ta-HKI/2023 concerning Copyright Infringement of Three-Dimensional Installations, the use of artistic creations for commercial purposes without prior permission from the creator is a copyright infringement. The Research problem in this article is 1) How does positive law in Indonesia regulate the legal protection of three-dimensional installation rights holders through UUHC 28/2014? and 2) Is the judge's assessment of UUHC 28/2014 in line with case Number 19 PK/Pdt.Sus-HKI/2023? This research is a normative descriptive legal research supported by interviews and secondary materials. Field research (interviews) and literature reviews are used to collect data, then conclusions are drawn through qualitative analysis using deductive methodology. The results and conclusion of the study show that based on the declarative principle, the protection of Article 40 paragraph (1) of the UUHC provides copyright and automatic protection for inventions. However, in Decision Number 3/Pdt.Sus-HKI/Cipta/2022/PN, Niaga Mks still violates Law 28/2014.